Value creation and risk management in mining operations through an integrated reporting framework of geotechnical data, uncertainty, and materiality - Zermatten, Carrie (University of the Witwatersrand, Johannesburg, 2025)
The research considers a stance that every aspect of the mining operation is, at its root, dependant on the geomechanical / geotechnical integrity of the excavation. A mining operation would not be able to maintain production if the excavated workings in the rock mass cannot be kept ‘open’ - even if many other aspects of the mine are very favourable (e.g. metallurgical and/or mineral processing can produce excellent recoveries, commodity prices are high etc). The research is compelled through several contributing factors, including the recognition that: • There is no national inventory of mining geotechnical data (viz. a comprehensive or extensive database) readily available to offer insight into the factual account of data provision that has supported viable mining operations to date. Such aspects would include the type, quantity, quality, and spatial distribution of data (as well as changes therein over time) associated with respective “types” of mineralised ore bodies, mining method selection, hydrogeological regime, etc. • The interpretation and application of scientific, engineering, and risk principles are often quite inconsistent within- and between- different mining operations. • The content and clarity of rock-related reporting is often highly variable - especially beyond the assessment of project viability to the actual performance over time of rock engineering, geomechanical stability, and geotechnical design dimensions of a mining excavation. • Practical realities in business (e.g. limited budget availability to particular cost centres, differing corporate priorities etc.) may limit the implementation of rock engineering decisions. The research identifies and compiles various information from a wide range of specialised topics that are commonly studied individually in smaller settings (e.g. rock mechanics, aspects prescribed under law, risk, subjective belief, governance as well as reporting transparency for mining projects [distinguished from the requirements of reporting of mineral resources and/or mineral reserves]). The topics are then related to each other, and their roles toward a holistic understanding of risk-related aspects of a mining operation are explored - with rock and geotechnical engineering as a central tenement of that consideration. The research advances the discourse of value creation and risk management in mining engineering, through: • The description of the complex interplay of components and organisations within the mining industry, as well as the potential for improving their coalescence. • The identification of opportunities created from reporting rock-related information and the demonstration of technical competence. These opportunities could be applied toward the goals of risk management, value creation, sustainability, and growing investor confidence. • The motivation that access to relevant geoscientific data is supported through the current regulatory framework; • Various geoscientific data could be retrospectively shared by mining organisations; and • The articulation of a proposition for voluntary disclosure. v Publications as part of this Research The publications that have been prepared from this research include: 1) The reporting of geotechnical data, uncertainty, materiality for hard rock mining operations. Additional publications that have been drafted and are being finalised, include: 1) Mandatory Codes of Practice in the South African Mining Industry. 2) An overview of legislated and regulated elements regarding ‘competency’ in mining operations. 3) An overview of the elements of section 54 and section 55 notices issued to South African mining operators. 4) What does it matter? An exploration of the language used in assessments wih regard to characteristics of risk-related elements. 5) Mining disasters and the resulting inquests undertaken to investigate and determine cause and responsibility. 6) An overview of the South African Mines Reportable Accidents Statistics System (SAMRASS). 7) 8) Mines Rescue Services of South Africa. 9) A comparison of mining rock-related, higher education learning programmes in South Africa, Australia, and Canada. 10) A comparison of the mining geotechnical elements required for reporting as part of the SAMREC Code, NI43-101 and JORC Codes. 11) An insight into various ‘risk reports’ generated by organisations across the globe, with interest in mining.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy in Engineering, in the Faculty of Engineering and the Built Environment, School of Mining Engineering , University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Value creation; risk management; geotechnical data; SDG-9: Industry, innovation and infrastructure; SDG-8: Decent work and economic growth